Nonsurgical Rhinoplasty: A Systematic Review of Technique, Outcomes, and Complications - Williams, Lauren C; Kidwai, Sarah M; Mehta, Karan; Kamel, George; Tepper, Oren M; Rosenberg, Joshua D (Plastic and reconstructive surgery (1963), 2020)
Nonsurgical rhinoplasty using filler injections has become a common procedure in cosmetic practices. This is offered to patients that prefer a temporary outcome or would like to avoid general anesthesia. In addition, it can be used in postrhinoplasty patients to correct nasal deformities or irregularities. This systematic review highlights common filler types and injection techniques, and associated patient satisfaction and complications to further guide practitioners. A systematic review was performed using keywords and Medical Subject Headings search terms. PubMed, EmBase, the Cochrane Library, and Scopus were searched using the appropriate search terms. Data collected from each study included patient satisfaction and complications, in addition to injection material, location, and technique. Four thousand six hundred thirty-two studies were found based on search criteria. After full-text screening for inclusion and exclusion criteria, 23 studies were included. A total of 1600 patients underwent nonsurgical rhinoplasty, most commonly with hyaluronic acid (73.38 percent), followed by calcium hydroxyapatite (12.44 percent). Nearly 95 percent of patients were satisfied with results, and there were only 26 relatively minor complications reported. There were no reports of vascular complications such as skin necrosis or visual compromise. Based on the authors' review of the literature, nonsurgical rhinoplasty is an effective temporary alternative to traditional augmentation rhinoplasty for corrections of nasal shape with a high degree of patient satisfaction. Complications may be underreported, and thus further investigation is needed to better understand the true incidence of major complications related to vascular compromise.